Persepsi Ancaman Amerika Serikat dalam Film-Film Hollywood Tahun 1960-2019 : Indonesia - Bima Sulihtra Hutama (Fakultas Ilmu Politik dan Ilmu Sosial, Universitas Brawijaya, 2023)
Film as a contemporary media today can not only be seen as entertainment but can be understood as a medium to convey the messages that people or parties behind the scenes want to convey, the message can be in the form of invitation, perception, and pseudo reality built by the maker. Threats are generally understood as any action that causes unrest to other parties, in international relations threats can be defined as situations where one actor or group has the ability or intention to cause negative consequences to other actors or groups seen from the perspective of the state, there are three categories of threats, namely domestic threats, transnational threats, and external threats. Threat perception is a concept in which there is a condition in which one actor feels threatened by the actions and circumstances of another actor, which in turn increases the perception of threat to the affected actor. Threat perception itself has four variables, namely aggregate power, proximity, offensive capability, and offensive intention. This research takes the span of 1960-2019 to see the transformation of threats in films which aims to find out how threat perceptions in films follow threat perceptions according to the United States by using resources in the field of Hollywood cinema. The researcher divides the research time in three eras, namely the cold war, post-cold war, and post-9/11 to see how the pattern of threat perception transformation in film. The researcher himself used mixed methods with the Explanatory Sequential Mixed Method Design model using quantitative to see and look for patterns and using qualitative to analyze quantitative results with the concept of threat perception applied in films.